Assessment of Agricultural Waste Energy Potential for Circular Economy and Biofuel Production - Alieksieieva, Olha; Lutkovska, Svitlana; Mazur, Kateryna; Hontaruk, Yaroslav (Dr. Viktor Koval, 2026)
Background. The transformation of agro-industrial waste into a strategic resource for energy decentralisation is crucial. In view of modern security challenges and the European Green Deal, there is a growing need for agro-industrial enterprises to transition to closed circular bioeconomy cycles, where intellectual capital and digitalisation serve as the basis for innovative progress. Purpose. The purpose is to provide a comprehensive assessment the potential for biofuel production from waste in the agricultural sector of Ukraine and justify its strategic role in ensuring energy independence, using a model to assess the technical and energy potential of biomass, taking into account environmental and logistical constraints. Findings. A model of the integrated technical and energy potential of the agro-industrial complex biomass was developed and tested based on ecological and technological screening principles for the period 2022-2025. The methodology considers the agro-ecological qualification (removal of no more than 25–30% of plant residues to preserve humus) and the institutional barrier of large-scale commercialisation (screening of dispersed waste from the private livestock sector), based on which the commercial potential of Ukrainian agro-biomass was determined at the level of 4.63 million tons of oil equivalent (toe) and its regional decomposition was carried out. The involvement of food industry enterprises (sugar and alcohol plants) as logistics hubs for biomethane and digestate production has optimised supply chains and reduced logistics costs by 30–40% compared to the decentralised collection of distributed biomass. Due to the concentration of significant volumes of homogeneous waste at the industrial sites of these enterprises, the maximum methane yield is achieved through co-fermentation, increasing the investment attractiveness of biogas projects and accelerating their payback. Implications. The effective conversion of agricultural waste into biofuels can significantly reduce the consumption of fossil resources (natural gas and coal) in local heat and power supply systems. The main barriers to the development of circular models are a lack of long-term investment capital and institutional restrictions on the integration of biomethane into the network. The practical significance of the results lies in the development of applied tools for government agencies and businesses to support regional energy development strategies and climate neutrality programs.